Primary systemic chemotherapy in locally advanced breast cancer- taxane versus non-taxane combination chemotherapy schedule - Anand, Aravindh S.; Francis, Biju U. (International Journal of Advances in Medicine, 2017)
Background: Primary systemic chemotherapy (PST) forms a pivotal role in the management of primarily inoperable locally advanced breast cancer (LABC). Studies have revealed that complete pathologic response (pCR) is a surrogate marker of survival of LABC patients. In this study we aim to compare two chemotherapy regimens TAC vs. FAC/FEC. Endpoints are pCR and toxicity. Methods: 130 primarily inoperable LABC patients who received PST with either taxane containing chemotherapy TAC (Docetaxe l75 mg/m2, Adriamycin 50 mg/m2, Cyclophosphamide 500 mg/m2) or non-taxane chemotherapy FAC (5-Flurouracil 500 mg/m2, Adriamycin 50 mg/m2, Cyclophosphamide 500 mg/m2)/FEC (5-Flurouracil 500 mg/m2, Epirubicin 100 mg/m2, Cyclophosphamide 500 mg/m2) were prospectively observed and studied as two treatment arms- Taxane arm (70 patients) or Non-taxane arm (60 patients). Patients in each arm received maximum 6 cycles of taxane or non-taxane chemotherapy. Tumor response & toxicity was assessed. Results: 25.7% patients in taxane arm and 10% patients in non-taxane arm had complete pathological response (p=0.014). 90% in taxane arm and 86.7% in non-taxane arm became operable after PST (p=0.564). Grade 3 or 4 neutropenia was seen in 45.7% and 3.3% in Taxane and non-Taxane arm respectively (p=0.000). All patients completed the planned treatment in spite of the higher incidence of Grade 3/4 neutropenia in the docetaxel arm. Conclusions:TAC has significantly better complete pathologic response with tolerable toxicity. Hence in Indian LABC patients as well, taxane containing chemotherapy in the primary setting is the better option. Longer follow up of this study may confirm whether the better pathologic response may translate to better survival.